1989
DOI: 10.1507/endocrj1954.36.721
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Prolactin and Rabbit Mammary Prolactin Receptor in the Presence of Environment-Modifying Agents.

Abstract: The binding assay of prolactin (PRL) to the receptor in the rabbit mammary gland was carried out with varying concentrations of NaCl, KCl, CaCl2, MgCl2, glycerol, glucose, sucrose and urea. The agents did not affect the binding capacity. The ionic bond-breaking agents (NaCl and KCl) had little effect on changes in the association rate constant (k+1) of PRL binding to the receptor and the dissociation rate constant (k_1) of bound PRL. The inclusion of other agents changed the k+1 and the k-1. Among the agents e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The data indicate that the PRL-receptor complex is further stabilized by contributions of hydrogen bonds and probably van der Waals contacts after the initial interaction. This is also supported by our previous findings showing that the PRL-receptor complex is unstable in the presence of hydrogen-bond-breaking agents (Sakai & Suzuki, 1989). Mammary PRL receptors have a high specificity for the binding of hormones.…”
Section: Free Energy Enthalpy Entropy Of Prl-receptor Reactionsupporting
confidence: 86%
See 2 more Smart Citations
“…The data indicate that the PRL-receptor complex is further stabilized by contributions of hydrogen bonds and probably van der Waals contacts after the initial interaction. This is also supported by our previous findings showing that the PRL-receptor complex is unstable in the presence of hydrogen-bond-breaking agents (Sakai & Suzuki, 1989). Mammary PRL receptors have a high specificity for the binding of hormones.…”
Section: Free Energy Enthalpy Entropy Of Prl-receptor Reactionsupporting
confidence: 86%
“…It appears that the first event is most appropriately described in terms of the 'hydrophobically bound complex' (terminology of Ross & Subramanian, 1981). The chaotropic agents interfered in the binding of PRL to its receptor by decreasing the k+1 of PRL binding to the receptor in a concentration-and agent-dependent manner (Sakai & Suzuki, 1989). Hydrophobic bonding appears to be the most important force participating in the PRL-receptor complex-formation.…”
Section: Free Energy Enthalpy Entropy Of Prl-receptor Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous results suggested that the PRL-receptor complex is further stabilized by the contributions of hydrogen bonds and probably van der Waals contacts after the hydrophobic interaction (Sakai & Suzuki, 1988;Sakai et al, 1990). It is expected that the PRL-receptor complex becomes less stable as the incubation temperature is increased.…”
Section: Discussionmentioning
confidence: 96%
“…At high concentrations, the k+1 decreased greatly, in the presence of bivalent cations. This is probably due to the alteration of the reaction environment (Sakai and Suzuki, 1989). Both Ca2+ and Mg2+ ions at high concentrations are known to have a chaotropic action.…”
mentioning
confidence: 99%